The Artificial Intelligence: Implication for The Identification and Protection of Child Victims of Deepfake - Musofiana, Ida; Virdaus, Saivol; Nur, Abdul Kholiq; Wicaksono, Dida Satria (Universitas Islam Sultan Agung, 2025)
Indonesia is the only nation that adheres to the Pancasila ideology, therefore it is natural to uphold human ethics and morals. However, the development of Artificial Intelligence technology has had a significant impact on various aspects of life, including the emergence of deepfake technology. This technology allows realistic manipulation of digital content, including the creation of illegal content such as child pornography. This phenomenon raises serious challenges in law enforcement, especially in Indonesia which is facing increasing cases of digital child exploitation. This research aims to examine legal aspects related to deepfake child pornography in Indonesia, identify challenges to law enforcement, and provide recommendations for strengthening legal regulations and implementation. This research aims to analyze law enforcement and tracking child victims of crimes using artificial intelligence. The analytical data processing in this research uses normative juridical studies, the results of secondary data processing are then analyzed as to how the phenomenon is in today's society. So appropriate analysis is expected to be produced to answer legal challenges facing current developments. The results show that it is essential to regulate a clear legal system regarding the protection and tracking of victims as well as legal ethics that are relevant to a civilized nation. This research presents a cross-disciplinary approach that combines artificial intelligence technology, cyber-criminal law, and child protection ethics, an area that has not been previously studied in an integrated manner in Indonesian legal literature. The focus on children as victims of deepfake content places this issue within the framework of protecting vulnerable groups based on cutting-edge technology.